Visualização de escoamento bifásico de líquido-gás em um rotor radial plano - Boschetto Junior, Alaor (2018)
There is frequent interest in the nuclear and oil industry in the study of two-phase flow of liquid-gas in centrifugal pumps. The understanding of the associated physical phenomena in the process of degradation of the common pump efficiency to this type of operation can give significant support in the optimization of centrifugal pumps used in nuclear reactors or in the artificial elevation of petroleum. Due to their importance, several studies have been developed to evaluate the liquid-gas flow in the degradation of the pressure gain curve of the pump and conditions in which the gas causes an unstable operation of the pump during its operation. However, there are few fundamental studies on the understanding of flow dynamics within centrifugal pump rotors when operating with two-phase flows. In this context, the present work will be carried out an experimental study, having as main focus the detailed visualization of the two-phase flow of liquid-gas in a radial flat rotor, in order to evaluate the physical phenomena involved from the acquired images. To meet the proposed study, an experimental bench was designed in which the radial rotor was constructed of transparent material to facilitate the visualization of the detailed behavior of the air flow in the rotor. The visualization will be performed using a high resolution camera fixed to the rotor axis, for different flow conditions (water and air) and rotation. From the acquired images, the flow will be classified by standards and associated to the tested operating conditions (flow, rotation). It was observed that for the increase of vacuum fractions and constant rotation speeds, the performance of the radial rotor is affected due to the formation of pockets of air inside the rotor. When the rotational speeds were changed to constant vacuum fractions, it has been observed that there is a coalescence of the air bubbles within the rotor with increasing speed of rotation.